PEMBERDAYAAN WARGA RT. 02 RW. 04 DUSUN SUMBEREJO DESA KINTELAN DALAM PENYULUHAN BAHAYA DIARE DAN CARA MENCUCI TANGAN YANG BENAR - Wahyu Ningsih, Arista Wahyu Ningsih; Wahyu Ningsih, Arista; Dinda Zulia Rahma; Ivan Charles; Dewi Rahmawati; Yani Ambari; Bella Fevi Aristia; Farida Anwari; Elis Anita Farida (Jurnal Bakti untuk Negeri, 2024)
Real Work Lecture activities are routine student activities as part of the educational process carried out by providing learning experiences for students to live in the midst of communities outside the campus and directly identify and deal with development problems faced. The Real Work Lecture activity for S1 Pharmacy students of Anwar Medika University was carried out in Kintelan Village, Sumberejo Hamlet, Rt.02 Rw.04, Puri District, Mojokerto Regency, East Java Province. The purpose of this service is to provide understanding to the local community about the importance of knowing the dangers of diarrhea and teach how to wash hands properly as one of the diarrhea prevention measures. The activity was carried out by educating residents of RT.02 RW.04 Kintelan Village using leaflet media. Pre-test and post-test are conducted to measure the understanding of residents before education compared to after education. The results and outcomes of the activity showed an increase in residents' understanding of diarrhea counseling from 72% to 94%.